2020
DOI: 10.1051/0004-6361/201936525
|View full text |Cite
|
Sign up to set email alerts
|

Upgraded antennas for pulsar observations in the Argentine Institute of Radio astronomy

Abstract: Context. The Argentine Institute of Radio astronomy (IAR) is equipped with two single-dish 30 m radio antennas capable of performing daily observations of pulsars and radio transients in the southern hemisphere at 1.4 GHz. Aims. We aim to introduce to the international community the upgrades performed and to show that IAR observatory has become suitable for investigations in numerous areas of pulsar radio astronomy, such as pulsar timing arrays, targeted searches of continuous gravitational waves sources, moni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 93 publications
1
37
1
Order By: Relevance
“…The analyses also consider the occurrence of pulsar glitches using different methodologies. For the Crab pulsar (J0534+2200), there were five glitches over the analysis period (see Section 3.2.2 and Section 2.1.1 of Abbott et al 2019a); for the Vela pulsar, there was a glitch between O2 and O3a (Gancio et al (2020) and references therein).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The analyses also consider the occurrence of pulsar glitches using different methodologies. For the Crab pulsar (J0534+2200), there were five glitches over the analysis period (see Section 3.2.2 and Section 2.1.1 of Abbott et al 2019a); for the Vela pulsar, there was a glitch between O2 and O3a (Gancio et al (2020) and references therein).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…In this work, we use the properties of J0437−4715high rotational stability, high luminosity, and short period-to assess the quality of the observations at IAR with both antennas. This builds upon the preliminary analysis presented in Gancio et al (2020) which suggested they reach a precision of 1 µs.…”
Section: Introductionmentioning
confidence: 54%
“…As described in more detail in Gancio et al (2020), the design of the antennas allows us to observe a source continuously over 220 minutes. Their receivers are not currently refrigerated and have a system temperature of T sys ∼ 100 K. The back-end is based on two softwaredefined radios which acquire raw samples with a maximum rate of 56 MHz per board.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations